Um museu vivo: memória e educação a partir das narrativas do povo Kanindé - Santos, Joselane Lima da Silva (2023)
This research consists of describing the narratives about the Kanindé Museum, a Museum built over the years by José Maria Pereira dos Santos, known to us as Cacique Sotero. The Kanindé Museum is a space for transformation and ethnic affirmation for the people, bringing a representation of something new, as it is characterized as a space that brings together, encourages, rescues and disseminates memory. In this study, it was possible to narrate the creation and management of the Museum and to analyze the importance and role of the Kanindé Museum in the social construction of memory, concepts and narratives of indigenous resistance. We investigated the Kanindé Indigenous Museum as a space for discussion around identity, we carried out an analysis from a contemporary perspective in anthropology that understands the issue of strengthening indigenous identity as a political project of resistance and protagonism of indigenous peoples in history, in the struggle for demarcation of our territories and for the recognition of our sociocultural difference. This research was built from practices and knowledge that involved field research, interviews, coexistence in the territory and classes that are developed at the Indigenous School Manoel Francisco dos Santos. A contribution is sought for a reflection on how an indigenous people does not destroy their acts of thinking and acting in the face of what is new. On the contrary, it reveals the dynamism of culture and social organization that every day produces more people's ability to interact with their own identity.